P1213ROLE OF PERITONEAL PHOSPHORUS TRANSPORT IN PERITONEAL DIALYISIS REGIMEN FOR THE MANAGEMENT OF HYPERPHOSPHATEMIA. (6th June 2020) - Xipell, Marc; Guillen Olmos, Elena; Rodas, Lida; Broseta, Jose J; Mayordomo, Angeles; Bonache, Debora; Maduell, Francisco; Vera, Manel
Abstract: Background and Aims: The ratio D/P-Creatinine (DP-Cr) obtained by the peritoneal equilibrium test (PET) is the most widely used parameter to characterize the type of peritoneal membrane transport, and it is used to determine the dialysis regimen for ultrafiltration (UF). It has been suggested that net UF influences the final clearance of solutes, so guiding ultrafiltration by D/P-Phosphorus (DP-P) instead of DP-Cr could have some added value in the management of hyperphosphatemia. The objective of this study is to define if there is a correlation between DP-P and DP-Cr, and if these are related to the clearance of phosphorus (P) and creatinine (Cr). Method: retrospective analysis of PETs performed during 2016 and 2017 in our center. DP-Cr and DP-P were calculated, and in patients with 24h effluent sample the day of the PET, it was also analyzed weekly Kt/V-urea, and peritoneal Cr and P clearance (CrCl and PCl, respectively). Statistical analysis was done using t-Student test for independent data and Pearson correlation coefficient, with SPSS Statistical Package program v.23, establishing a significance level of p<0.05. Results: 68 PETs were analyzed in 54 patients, mean age 60.4 years (SD 17), predominantly men (69% vs 31%). The mean plasma P, DP-Cr and DP-P were respectively 4.5 mg/dL (SD 1.2), 0.74 (SD 0.12) and 0.71 (SD 0.17). The correlation coefficient DP-P/DP-Cr showed a significant relationship (r=0.84, p<0.001), which was maintained when analyzing patients according to phosphorus levels: DP-P/DP-Cr with P<5 mg/dL (r=0.81); and P≥5 mg/dL (r=0.93) (p<0.001).Patients in DP-P ≥50th percentile had P levels of 4.2 (± 1.05), and those in<50th percentile had levels of 4.88 (± 1.38) (p <0.031). Moreover, in patients with 24h effluent analyzed the day of the PET (n=35), the average PCl and CrCl was 4.1 and 2.85 ml/min, with statistical significant correlation (r=0.92, p<0.001).However, in these patients no relationship was found between DP-Cr and CrCl (r=0.068, p=0.7), nor between DP-P and PCl (r=0.052, p=0.7). Conclusion: The DP-P/DP-Cr high correlation suggests that both parameters could be useful to classify the type of peritoneal transport. However, although patients with higher DP-P had better control of hyperphosphatemia, thus suggesting a direct positive relationship between DP-P and PCl, our data showed no correlation between them.